The Effect Of Milk Kefir With Sorgum Flour On Body Weight, Appearance, And Abdominal Fat In Mice Obesity Induced - Indri Dewi Listiani; Rizki Nurmalya Kardina (Journal of Food and Pharmaceutical Sciences, 2022)
In obese patients, one way to prevent obesity with the right method is to modulate the intestinal microflora. The purpose of this study was to identify and analyze the differences in administration of milk kefir with additional sorghum flour on body weight, appetite, and abdominal fat in mice (Mus musculus) induced obesity.This type of research is a true experimental in vivo using a randomized controlled design pretest – posttest control group design. The experimental animals used were 34 healthy mice (Mus musculus). Data analysis with normal distribution was tested by One Way Anova, otherwise Kruskal Wallis was tested. Meanwhile, categorical data were tested Univariate. The results showed that in the third treatment (P3) mice experienced differences in the treatment given milk kefir with the addition of sorghum flour and high fat diet feed for 8 weeks or 56 days there was a difference in weight loss as measured by weight gain (p<0.05), then there wasn’t difference in appetite (p>0.05), while there was a difference in abdominal fat compared to the control group. So, for those who are obese, it’s expected that milk kefir products with sorghum can be used as a daily drink to help reduce body weight and abdominal fat.